Executive summary - Csapó, Benő; Funke, Joachim; Schleicher, Andreas (The nature of problem solving, 2017)
Problem solving is one of the key competencies humans need in a world full of changes, uncertainty and surprise. It is needed in all those situations where we have no routine response at hand. Problem solving requires the intelligent exploration of the world around us, it requires strategies for efficient knowledge acquisition about unknown situations, and it requires creative application of the knowledge available or that can be gathered during the process. The world is full of problems because we strive for so many ambitious goals – but the world is also full of solutions because of the extraordinary competencies of humans who search for and find them.